Pengaruh employee engagement terhadap kinerja perawat - Laura Desinda Sutondo Putri; Risa Setia Ismandani; Warsini Warsini; Rizki Aqsyari (THE JOURNAL OF Nursing Management Issues, 2026)
Background: Nurse performance is an important aspect of maintaining service quality, particularly in intensive care units with high workloads. Nurses face physical and psychological pressures that may affect their performance. In addition, disparities in nurse performance exist, as reflected by some nurses performing optimally while others demonstrate lower levels of responsibility. This condition may create a sense of unfairness and reduce employee engagement among nurses. Purpose: To determine the effect of employee engagement on nurse performance in the intensive care unit of Dr. Moewardi Hospital. Methods: This study employed an analytical quantitative design with a cross-sectional approach. The study population included all nurses working in the intensive care unit of Dr. Moewardi Regional General Hospital, with a sample of 142 respondents determined using the Krejcie and Morgan Table. Data were collected using a questionnaire and analyzed using the chi-square test Results: There was a significant association between employee engagement and nurse performance (OR = 2.205; 95% CI = 1.461–3.326; p = 0.001). Conclusions: Positive work engagement plays an important role in supporting the performance of nurses in carrying out their duties and responsibilities optimally, especially for nurses in intensive care units. Keywords: Employee engagement; Nurse performance; Nurses. Pendahuluan: Kinerja perawat merupakan aspek penting dalam menjaga mutu pelayanan, khususnya di unit perawatan intensif yang memiliki beban kerja tinggi. Perawat dihadapkan pada tekanan fisik dan psikologis yang dapat memengaruhi kinerjanya. Selain itu, terdapat ketimpangan kinerja antar perawat, yang ditunjukkan oleh sebagian perawat bekerja secara optimal, sedangkan sebagian lainnya kurang bertanggung jawab. Kondisi ini dapat memicu rasa ketidakadilan dan menurunkan tingkat engagement antar perawat. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh employee engagement terhadap kinerja perawat di unit perawatan intensif RSUD Dr. Moewardi. Metode: Penelitian ini menggunakan desain kuantitatif analitik dengan pendekatan cross-sectional. Subjek penelitian meliputi seluruh perawat di unit perawatan intensif RSUD Dr. Moewardi dengan sampel 142 responden yang ditentukan berdasarkan Table Krejcie and Morgan. Data dikumpulkan menggunakan kuesioner dan dianalisis menggunakan uji chi-square. Hasil: Terdapat hubungan yang signifikan antara employee engagement terhadap kinerja perawat. (OR = 2.205 ; CI 95% = 1.461 – 3,326 ; p-value = 0.001).  Simpulan: Keterlibatan kerja yang positif memiliki peran penting dalam mendukung kinerja perawat untuk menjalankan tugas dan tanggung jawab dengan optimal khususnya bagi perawat di unit perawatan intensif. Kata Kunci: Keterikatan karyawan; Kinerja perawat; Perawat.